Correlation between results of explosive strength and speed tests in young football players - Bubnjević Petar; Vukićević Veljko; Lukić Nikola; Miličković Velimir (College of Sports and Health, Belgrade, 2020)
The subject of this research are the motor skills of children of preschool, younger school and middle school age who train football. The aim of the study was to establish the level of correlation of the observed tests in different age categories, as well as the influence of morphological characteristics on motor test results in subjects of different age. To assess morphological characteristics: body height and body weight, and three variables - foot tapping for 15 seconds, standing long jump and 30m sprint tests were used. The study involved transversal research conducted on a sample of 40 boys of preschool, younger school and middle school age (6-13 years old), who actively played football in the "Jedinstvo" school of football from Gospodjinci. The training experience of the respondents ranges from 6 months to 5 years. The obtained results indicate that there is no statistically significant correlation between explosive strength and speed tests in preschool age, while in younger school age the statistical correlation is significant, and in middle school age the correlation is the greatest. The obtained results confirmed that the level of connection between motor tests changes depending on the age of the examinees. Body height and body weight were found to have a statistically significant effect on the results of the long jump and 30m sprint tests only in middle school age. This type of statistically significant influence of body height and body weight on the results of motor tests was not observed in preschool and younger school age.